2011
DOI: 10.5694/mja11.10192
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early paternal depression on children's development

Abstract: Main outcome measure: Child scores on the Strengths and Difficulties Questionnaire and on a set of Derived Outcome Indices, measured when the child was 4-5 years old. Logistic regression modelling was used to investigate how early paternal depression in 2004 influenced child outcomes 4 years later.Results: Early paternal depression was a significant predictor of a range of poorer child outcomes (odds ratio [OR] Conclusions: Depression in fathers during the first year of a child's life can have a detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 20 publications
5
94
0
Order By: Relevance
“…Recent research has shown that depressed fathers are 4 times as likely to spank their infants than nondepressed fathers and less likely to read to them. 105,119 Fathers' ratings of 16 domains/ activities of their lives ranked the emotional experience of parenting along with work-life conflict as the most negative and the most tiring activities. 120 Longitudinal studies of paternal depression scores from the National Longitudinal Health Survey showed the highest score for nonresident fathers on entry to fatherhood.…”
Section: Influence Of Fathers' Mental and Physical Well-being On Chilmentioning
confidence: 99%
“…Recent research has shown that depressed fathers are 4 times as likely to spank their infants than nondepressed fathers and less likely to read to them. 105,119 Fathers' ratings of 16 domains/ activities of their lives ranked the emotional experience of parenting along with work-life conflict as the most negative and the most tiring activities. 120 Longitudinal studies of paternal depression scores from the National Longitudinal Health Survey showed the highest score for nonresident fathers on entry to fatherhood.…”
Section: Influence Of Fathers' Mental and Physical Well-being On Chilmentioning
confidence: 99%
“…7 There are fewer studies that have investigated the impact of paternal depression on children; however, those that have also show consistent associations between paternal depression postnatally and an increased risk of behavioral and emotional problems in children between 3 and 5 years old. [8][9][10] Children of fathers with depression had higher rates of such problems than children whose fathers had not been depressed (16.9% vs 8.5%). 9 Despite the reported associations between depression in parents and adverse child outcomes, there is only limited information about the mechanisms by which any risk is transmitted from parents to children or whether there are factors that moderate the potential impact.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[1][2][3][4][5] Depressed fathers exhibit poorer parenting behaviors, 6 lower likelihood of child engagement, and greater likelihood of parenting stress and child neglect 7 than non-depressed fathers. 8 Children of depressed fathers are at risk for later psychiatric disorders, 3 poorer language and reading development, 9 and increased risks of behavior problems, including peer problems, conduct problems, and poorer prosocial behaviors across ages, than children of nondepressed fathers.…”
mentioning
confidence: 99%
“…8 Children of depressed fathers are at risk for later psychiatric disorders, 3 poorer language and reading development, 9 and increased risks of behavior problems, including peer problems, conduct problems, and poorer prosocial behaviors across ages, than children of nondepressed fathers. 2,5 Although studies show a decline in young men' s physical health during the transition to fatherhood, [10][11][12] less is known about the mental health of fathers during the transition. Several social factors may be implicated.…”
mentioning
confidence: 99%